Monitoring dan Evaluasi Kegiatan Penanaman Mangrove (Kasus: Desa Sebuntal, Kabupaten Kutai Kartanegara) - Ritonga, Irwan Ramadhan; Budiarsa, Anugrah Aditya; Eryati, Ristiana; Novia, Rani; Ahmad, Ahmad; Firman, Firman; Silviana, Silviana; Main, Aminullah Aminul; Akbar, Rizali; Saputra, Dharma; Soenarih, Asih; Tobing, Binto Iskandar Hasibuan; Apriliyani, Vivi; Aprilia, Dita; Rafi’i, Ahmad (Universitas Tanjungpura, 2024)
Damage to mangrove ecosystems in coastal areas could result in biotic and abiotic physical changes. This damage might occur due to natural factors or human activities. Among the damaged mangrove ecosystems in East Kalimantan Province is Sebuntal Village. The aim of this research is to monitor and evaluate the survival rate of mangrove seedlings in Sebuntal village, Kutai Kartanegara Regency. The research population used in this research was all mangrove seedlings (Avicennia spp) planted during community service activities on August 9th, 2023. The research method used in this study was the survey method. It was found that the survival rate in this study was only 8.2%. This research showed that individual mangroves' survival rates were unsuccessful due to inappropriate planting times, hydro-oceanographic patterns that are poorly studied, and poor seed preparation.